Relative Measures of Genocide Mortality : Benefits and Methodological Considerations of Using Siblings' Survival Data - de Walque, Damien (Taylor and Francis, 2020)
When studying events such as the 1994 Genocide in Rwanda, for many researchers the first order question seems to be to find the best available data and methods to estimate the death toll, i.e. to provide a number of deaths in absolute terms. This makes sense since the staggering number of victims over a very short period is one of the most shocking – and defining – features of such an historical event. This short note argues that while looking for an absolute death toll number is certainly an important and worthwhile research exercise, analyzing relative mortality numbers also provides valuable insights that might not be available when focusing on absolute numbers. By relative mortality I mean comparing mortality across different population segments such as by gender, by age group or socioeconomic categories (e.g. education levels, urban/rural background). Specifically, I will use the examples of the Khmer Rouge Period in Cambodia (1975-1978) and the 1994 Genocide in Rwanda to illustrate this argument and will rely on earlier studies to show how the sibling mortality schedule – a module collecting information about the date of birth, the sex and if relevant the date of death of all siblings of the respondent – contained in most of the well-known and commonly used Demographic and Health Surveys (DHS) can be exploited to obtain reasonable and useful estimates of relative mortality.